2020
DOI: 10.1007/s00384-020-03765-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin usage and the risk of colorectal cancer: a national cohort study

Abstract: Purpose This study aimed to investigate the association between metformin usage and the risk of colorectal cancer (CRC) using data from the Korean National Health Insurance Service-National Health Screening Cohort database. Methods Data from the NHIS-HEALS cohort between 2002 and 2015 were longitudinally analyzed. Subjects were divided into three groups: metformin non-users with diabetes mellitus (DM), metformin users with DM, and no DM group. CRC was defined using the ICD-10 code (C18.0-C20.0) at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Although the cancer-preventive effects of metformin remain controversial, its usage and subsequent reduction of cancer risk has been seen in certain cancer patients, particularly those subjects possessing a diabetic background [ 13 , 15 , 37 , 38 ]. To simulate clinical situations involving metformin prescription and use, experimental models of tumor growth in rodents have yielded promising evidence showcasing the anticancer potential of metformin [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cancer-preventive effects of metformin remain controversial, its usage and subsequent reduction of cancer risk has been seen in certain cancer patients, particularly those subjects possessing a diabetic background [ 13 , 15 , 37 , 38 ]. To simulate clinical situations involving metformin prescription and use, experimental models of tumor growth in rodents have yielded promising evidence showcasing the anticancer potential of metformin [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Algire et al [ 27 ] found that metformin had an inhibitory effect on tumor growth in C57BL/6 mice fed with HFD, while a limited effect was observed in C57BL/6 mice fed with a normal control diet. Although metformin use and its ability to reduce cancer risk are found in cancer patients [ 13 , 15 , 37 , 38 ], the aforementioned controversy indicates that metformin may only offer benefits to certain cancer populations with remarkable metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is the first-line type 2 diabetes mellitus treatment that works by reducing insulin resistance and fasting plasma insulin levels, leading to a reduction in blood glucose concentrations without causing overt hypoglycemia [12]. Several observational studies have shown that metformin may also reduce cancer risk and improve the prognosis and survival of cancer patients [62][63][64]. The plausible mechanisms that explain this association focus largely on inhibiting growth stimuli and metabolic processes within cancer cells and can be divided into insulin-dependent and -independent mechanisms that alter cancer cell growth [65].…”
Section: Metforminmentioning
confidence: 99%
“…Supplemental digital content 1, http://links.lww.com/ACD/ A419 showed study characteristics. Eight case-control studies [11][12][13][14][15][16][17][18] (including 22050 CRC patients and 48 4594 controls), 19 cohort studies [9,10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (including 43 7688 metformin users and 118 3331 no-metformin users) and 1 randomized controlled trial (RCT) (including 71 metformin users and 62 no-metformin users) detected the effect of metformin use on the risk of CRC in DM. Additionally, 2 case-control studies [36,37] (including 400 CRC patients and 345 controls) and 6 cohort studies [38][39][40][41][42][43] (including 3938 metformin users and 3338 no-metformin users) detected the effect of metformin use on all-cause mortality of CRC in DM.…”
Section: Study Characteristicsmentioning
confidence: 99%